Prevalence of bovine tuberculosis and its zoonotic implication in and around Bonga town, south west Ethiopia - Addisu, Solomon; Abebe, Belay (Asian Journal of Medical and Biological Research, 2020)
A cross sectional study was conducted from October 2013 to April 2014 G.C on 384 heads of dairy cattle and 107 cattle owners, in and around Bonga town, south west Ethiopia. Comparative intra dermal tuberculin test and questionnaire survey were carried out to determine the prevalence of bovine tuberculosis and to assess its zoonotic implication, respectively. Systematic random sampling technique was used to conduct the comparative intra dermal tuberculin test. Multivariate logistic regression model was used to analyze the data. Accordingly out of 384 heads of dairy cattle the overall prevalence was estimated to be 1.56 % (6/384). Using 95% confidence interval statistically significant variables were observed among sign of chronic cough with progressive wastage of body condition (P=0.043) and the origin of dairy cattle (P=0.039). While simple random sampling technique was used to select cattle owners for interview and 107 were participated. Analysis of retrospective data of six and half years on human TB collected from Bonga general hospital revealed significant level of TB cases. From the total TB patients, 56% had pulmonary form of TB, while 44% had extra pulmonary form of TB patients registered. The result of the present study has revealed that relatively low prevalence of BTB in dairy cattle and poor awareness of the respondents on zoonotic implication of bovine tuberculosis. There should be segregation and practice of boiling of raw milk before consumption at home and awareness creation should be done for the whole society about bovine tuberculosis and its mode of transmission. Asian J. Med. Biol. Res. March 2020, 6(1): 107-122